Kıbrıs türk romanında Göç (1963-2010) - Aylanç, Mihrican (My University, 2011)
Bu çalışmada Kıbrıs Türklerinin toplumsal tarihinde önemli yer eden göçlerin Kıbrıs Türk romanına yansıma şekilleri üzerinde durulacaktır. Adaya 1571’de sürgün yoluyla zorunlu olarak göç ettirilen Kıbrıs Türkleri, I.Dünya Savaşı’ndan sonra, çeşitli dönemlerde farklı etmenlere bağlı olarak gelişen göç süreçleri yaşamışlardır. 1974’e kadar adada varoluş mücadelesi sürdüren Kıbrıs Türkleri, üç ayrı dönemde zorunlu iç göçler yaşamışlar, büyük ölçüde eğitim, üretim ve ekonomik yaşantının dışında kalmış ve dış göçlere başvurmuşlardır. Adada sürekli hareket halinde olmuşlar ya da harekete endeksli bir hayat sürmüşlerdir. Kıbrıs Türklerinin toplumsal tarihi savaş ve göçlerle şekillenmiştir. Büyük ölçüde tarihî olayların, ferdî tecrübelerin yazıya aktarılmasıyla oluşan ve “yaşantı edebiyatı” olarak nitelendirilebilecek Kıbrıs Türk romanları Kıbrıs Türklerinin toplumsal tarihinde önemli yere sahip olan göçleri irdelerler. Göç süreçlerine; göç nedenleri, göç şekilleri ve göç sonuçları olarak geniş yer verirler. Göç sonrasında ortaya çıkan uyum sorunlarını toplum merkezli yaklaşımlarla irdelerler. Göç ve değişim süreçlerini yansıtan romanlar, toplumsal tarihe tanıklık etme işlevini üstlenirler.

The migration of the Turkish Cypriots carries great importance in their history and this study focuses on the reflections of this experience on the Turkish Cypriot novel. Forced to migrate to the island in 1571, the Turkish Cypriots experienced several immigration periods in connection with various factors evolving during the time after the First World War. Until 1974, the Turkish Cypriots carried on a struggle for survival, being forced to endure both inland immigration at three different time intervals, and unfortunately outbound immigration as well, due to the deprivation they suffered in areas related to education, production and economics. In short, they were either constantly on the move, or leading a life on the verge of action. The societal history of the Turkish Cypriots has been moulded with wars, struggles and migrations. The Turkish Cypriot novel, which can also be referred to as ‘life literature’ (yaşantı edebiyatı) mainly reflects on historical events and personal experiences and scrutinizes the movements of the Turkish Cypriots, which plays an important part in their life. It approaches and analyses the course, reasons, mode and results of these movements extensively. What’s more, the Turkish Cypriot novel examines via a community-centred approach, the adaptation problems that arise in the post-migration period. In summary, novels that reflect the course of migration and change undertake the responsibility of being the witnesses of societal history.
Keywords: Göçler_Anadolu; Türk Romanı; Türk Romanı_Göçler